2014
DOI: 10.1016/j.neuropharm.2013.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged nicotine exposure down-regulates presynaptic NMDA receptors in dopaminergic terminals of the rat nucleus accumbens

Abstract: The presynaptic control of dopamine release in the nucleus accumbens (NAc) by glutamate and acetylcholine has a profound impact on reward signaling. Here we provide immunocytochemical and neurochemical evidence supporting the co-localization and functional interaction between nicotinic acetylcholine receptors (nAChRs) and N-methyl-D-aspartic acid (NMDA) receptors in dopaminergic terminals of the NAc. Most NAc dopaminergic terminals possessed the nAChR α4 subunit and the pre-exposure of synaptosomes to nicotine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 71 publications
1
36
1
Order By: Relevance
“…Three possible indirect routes for this action were considered; via GABAergic systems, given the abundance of GABAergic medium spiny neurones and interneurons in NAc, via cholinergic mechanisms, on the basis of the evidence showing cholinergic modulation of dopamine release in the striatum 10,13,23,24,25 or through mGluR-mediated mechanisms, since mGluR group 2 and 3 receptors are widely distributed in striatal areas, have been shown to be inhibitory, and they decrease dopamine release, probably through presynaptic receptors located on dopamine terminals 29,30 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Three possible indirect routes for this action were considered; via GABAergic systems, given the abundance of GABAergic medium spiny neurones and interneurons in NAc, via cholinergic mechanisms, on the basis of the evidence showing cholinergic modulation of dopamine release in the striatum 10,13,23,24,25 or through mGluR-mediated mechanisms, since mGluR group 2 and 3 receptors are widely distributed in striatal areas, have been shown to be inhibitory, and they decrease dopamine release, probably through presynaptic receptors located on dopamine terminals 29,30 .…”
mentioning
confidence: 99%
“…The effects were blocked by the NMDA-R antagonist AP-5, indicating a specific, NMDA-R mediated mechanism, but not by picrotoxin, indicating that an intermediary action via GABA-A receptors is unlikely. Cholinergic systems are known to modulate of striatal dopamine release, through both nicotinic and muscarinic mechanisms 13,23,24,25 . In the present study we found that the α4β2 nicotinic antagonist, DHβE, attenuated the NNDA-R evoked suppression of stimulated dopamine release.…”
mentioning
confidence: 99%
“…Nicotine self-administration may result in increased NR2B NMDA subunit expression in NAc shell, although these changes did not reach significance [228]. In contrast, nicotine exposure has been shown to downregulate NR2B-containing NMDA subunits on nAChR-expressing dopaminergic terminals in NAc synaptosomes [229]. Moreover, nicotine self-administration is associated with decreased mGlu2/3 receptor expression in the NAc shell [93].…”
Section: Neurophysiological Mechanisms Underlying Nicotine-seeking Bementioning
confidence: 99%
“…nACh receptors cooperate with coexisting presynaptic NMDA receptors in the facilitation of noradrenaline and dopamine release in hippocampal and striatal nerve terminals, respectively [145,146]. In contrast, nicotine has been reported to evoke internalization of presynaptic NMDA receptors in dopaminergic terminals of the rat nucleus accumbens resulting in decreased NMDA-induced dopamine release [147]. On the other hand, nicotine pretreatment increased the responses of the NMDA receptors, which contain the GluN2A subunits, via activation of α7-nACh receptor subtypes on the glutamatergic nerve endings of the nucleus accumbens [148].…”
Section: Modulation Of Nmda Receptors By Acetylcholinementioning
confidence: 99%